2017
DOI: 10.1080/02656736.2017.1361048
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and thermal ablation for malignant thyroid tumours

Abstract: Papillary thyroid carcinoma (PTC) is the most common subtype of thyroid malignancy and has a good prognosis and low mortality rate. Surgery is the standard treatment for patients with primary and recurrent thyroid cancer. Although patients with PTC usually exhibit excellent treatment outcome, the incidence of recurrence in the neck ranges from 20% to 59%. When a patient with thyroid cancer is contraindicated for surgery, ultrasound (US)-guided ablation techniques, including ethanol ablation (EA) and thermal ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 68 publications
(210 reference statements)
0
48
0
Order By: Relevance
“…Recently, treatment of mPTC with ablative techniques such as laser, radiofrequency, microwave or percutaneous ethanol injection has been reported (38)(39)(40)(41). Although studies have demonstrated the shortterm efficacy and safety of these procedures, it is the current opinion of this panel that there is no evidence of their superiority over active surveillance in patients who are candidates for the latter, or of their superiority over surgery when it is indicated and feasible.…”
Section: Recommendationmentioning
confidence: 99%
“…Recently, treatment of mPTC with ablative techniques such as laser, radiofrequency, microwave or percutaneous ethanol injection has been reported (38)(39)(40)(41). Although studies have demonstrated the shortterm efficacy and safety of these procedures, it is the current opinion of this panel that there is no evidence of their superiority over active surveillance in patients who are candidates for the latter, or of their superiority over surgery when it is indicated and feasible.…”
Section: Recommendationmentioning
confidence: 99%
“…As an alternative option to surgery, image guided ablation has the advantage of minimal invasiveness, and had been successfully performed using different techniques in the past few years, including ethanol ablation [7], radiofrequency ablation (RFA) [8], microwave ablation [9], laser ablation [10] and so on. Among those techniques, RFA was most commonly applied and had been proved to be safe and effective for the treatment of benign thyroid nodules [8], and a recently published guideline based on Delphi method suggested that thermal ablation may be proposed as a first line treatment for solid nonfunctioning thyroid nodules that are benign at cytology when they become symptomatic [11].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of tumor complete disappearance ranged from 25% to 94% of cancers with an improvement in therapeutic success and symptoms ranging from 75% to 97% and 64%, respectively. Moreover, in many patients a decrease in serum thyroglobulin concentration was described (88,(102)(103)(104)(105)(106)(107)(108)(109)(110)(111). A recent metaanalysis made by Suh et al compared the effectiveness and safety of RFA and PEI for the treatment of total sample size of recurrent thyroid cancers in 270 patients with a VRR ≥50% rate of 100.0% after RFA and of 89.5% after PEI associated to a rate of complete disappearance of the nodules of 68.8% and 53.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%